Management of Acute Pulmonary Edema in Kidney Transplant Patients in the ICU - Ginting, Muhammad Aldi Rivai Ginting; Suwarman, Suwarman (Journal of Society Medicine, 2025)
Introduction: Kidney transplantation is the standard treatment for end-stage renal disease (ESRD), significantly improving survival rates and quality of life. However, pulmonary complications are a leading cause of morbidity and mortality post-transplant. Case Report: This case report presents a 50-year-old male with chronic kidney disease (CKD), diagnosed five months prior and undergoing regular hemodialysis. He had a history of hypertension and diabetes mellitus. The patient underwent a 9-hour kidney transplant surgery without complications. Post-operatively, urine output was minimal (5 mL), prompting vasopressor support to elevate the mean arterial pressure above 150 mmHg, which improved renal function. On days one and two post-surgery, the patient developed respiratory distress, with a chest X-ray revealing pulmonary edema. Continuous furosemide infusion was initiated to manage fluid overload, leading to improvement in the patient’s respiratory status. By day four, the patient was stable and transferred from the ICU to a regular room. Pulmonary complications, including pulmonary edema, affect up to 80% of kidney transplant recipients in the first year post-transplant and contribute to high morbidity and mortality. Conclusion: This case emphasizes the importance of early recognition and management of pulmonary edema through fluid management and vasopressors. Timely intervention, including diuretic therapy, is crucial for stabilizing kidney transplant recipients and improving patient outcomes. The report highlights the need for further research to establish evidence-based guidelines for fluid management in kidney transplant patients. Effective management is essential for enhancing post-operative recovery and quality of life in transplant recipients.